Faktor - Faktor Yang Berhubungan dengan Kejadian Obesitas Pada Siswa MAN 1 Kota Padang - Alfita Dewi; Ilma Nuria Sulrieni; Melvia Solfia Ningsih (Yayasan Literasi Sains Indonesia, 2023)
Data from the Padang City Health Office recorded a recapitulation of the results of the health screening of student examinations in the City of Padang in 2021 in the nutritional status assessment examination as many as 209 students experiencing obesity in twenty-three health centers, of which 54 cases of obesity were found at the Ambacang Health Center in Padang City. This study aims to determine the factors associated with the incidence of obesity in MAN 1 Padang students in 2022. This type of research is analytic with cross sectional design. This research was conducted at MAN 1 Padang on September 27 to October 10, 2022. The population of this study were all students of class XI, totaling 304 people with a total sample of 173 people. The sampling method used proportional random sampling technique. Data was collected using a questionnaire by means of interviews. Data processing was carried out univariate and bivariate with Chi Square test using SPSS program. Based on the results of the study, it was found that 67.1% of students were obese, 71.1% of students had bad eating patterns, 67.1% of students experienced low levels of knowledge and 57.8% of students chose fast food consumption. Chi Square test results obtained p value = 0.000 > = 0.05 (diet), p value = 0.000 < = 0.05 (level of knowledge) and p value = 0.035 < = 0.05 (Fast Food Consumption ). Based on the research, it can be concluded that there is a relationship between eating patterns, level of knowledge and consumption of fast food with the incidence of obesity. it is hoped that the school can provide counseling about the factors that can cause obesity.